Aesthetic experience and somaesthetics - Shusterman, Richard. (Studies in Somaesthetics, 2018)
This collection of essays explores the crucial connections between aesthetic experience and the interdisciplinary field of somaesthetics, while further advancing inquiry in both. After the editor's introduction and three articles examining philosophical accounts of embodiment and aesthetic experience in existentialism, phenomenology, hermeneutics, and pragmatism, the book's nine remaining articles apply somaesthetic theory to the fine arts (including detailed studies of the body's role in painting, sculpture, architecture, poetry, music, photography, and cinema) but also to diverse arts of living, considering such topics as cosmetics and sexual practice. These interdisciplinary, multicultural essays are written by a distinctively international group of experts, ranging from Asia (China and India) to Europe (Denmark, Finland, Hungary, and Italy) and the United States.